Homeotic Genes: Clustering, Modularity, and Diversity - Hajirnis, Nikhil; Mishra, Rakesh K. (Frontiers in Cell and Developmental Biology, 2021)
Hox genes code for transcription factors and are evolutionarily conserved. They regulate a plethora of downstream targets to define the anterior-posterior (AP) body axis of a developing bilaterian embryo. Early work suggested a possible role of clustering and ordering of Hox for regulating their expression in a spatially restricted manner along the AP axis. However, the recent availability of a large number of genome assemblies for different organisms uncovered several examples which defy this constraint. Keeping in mind the latest discoveries in the past decade, the current review discusses the arrangement of Hox in different organisms. Further, we revisit their discovery and regulation in Drosophila melanogaster. We also review their regulation in different arthropods as well as vertebrates with a major focus on Hox expression in crustacean Parahyale hawaiensis. It is noteworthy that subtle changes in the levels of Hox gene expression can contribute to the development of novel features in an organism. We, therefore, delve into the distinct regulation of these genes during primary axis formation, segment identity, and extra-embryonic roles such as in the formation of hair follicles, or, misregulation leading to cancer. Towards the end of each section, we emphasize the possibilities of several experiments involving various organisms, owing to the advancements in the field of genomics and CRISPR-based genome engineering. Overall, we present a holistic view of the functioning of Hox in the animal world.